Linking environment, democracy and gender - Wejnert, Barbara (Bingley, U.K. : Emerald, 2012)
This volume highlights the ways in which scholarly analysis has contributed to a rich understanding of the links between spreading democracy, gender equality, and environmental protection. Combining theoretical, empirical, and policy perspectives, the volume includes cutting-edge debates on the meaning of democracy and the processes of its development, as well as the response of democracies to environmental and gender concerns. In particular, the volume answers questions applicable to the situation of women in the democratizing world as well as to environmental problems, linking together the issues of gender and environment. It discusses the difference between democratic and non-democratic countries in terms of protection and care for their citizens; security of women's rights and women's opportunities offered by democratic vs. non-democratic states; relations between environmental issues and gender; and women's response to environmental problems.
Democratization and citizenship : the gender dimensions of political representation in Nigeria / J. Shola Omotola -- The Russian dacha : a repository of civil indifference / Ernest Raiklin -- Gender and democracy : an overview for Nepal / Shiba S. Banskota -- Internet autobiographies : female politicians' representations of gender / Sheri Kunovich, Amanda Wall -- On the relevance of the principal programs of the leading post-Soviet Russian political parties / Ernest Raiklin -- Women in Poland : transition to democracy and stereotypes / Elzbieta Sawa-Czajka -- Empowering women using environmentally friendly technology in paper recycling / Nirupama Prakash -- The strength of face-to-face contacts, personal ties, and institutional links in building democracy : the case of dissident movement in Eastern Europe / Barbara Wejnert -- Why there is a need to study democracy when linking environment and gender? : the case of environmental disasters / Barbara Wejnert.
Print version record
Keywords: Political Science -- General; Political Science -- Political Freedom & Security -- International Security; Political Science -- Peace; Political science & theory; Political economy; Political sociology